Nutritive value of forages as affected by soil and climatic differences. - Koch, B.A.; Smith, E.F.; Richardson, D.; Cox, R.F.; Ordoveza, A. (Kansas Agricultural Experiment Station, 2011)
This report is a summary of progress to date in one phase of the study designed to determine differences in the results obtained when cattle consume forage grown on limestone or sandstone soils. In any study of this sort there are many variables which cannot be completely controlled or eliminated. Regardless of the care used in selection pastures and meadows will differ somewhat in type and yield of forage: Rainfall differs, even on pastures within a few miles of each other. And the previous histories of the pastures are somewhat different All these and many other variables affect the results obtained. Therefore, several years of comparisons will be needed before definite conclusions can be drawn. Results obtained to date should be looked upon as suggestive rather than as final conclusions.
Keywords: Beef; Nutritive value; Soil; Climate